Strengthening Lifelong Education For Development: The Case of Ghana - Oduro-Mensah, D.; Biney, I.K. (PAACE Journal of Lifelong Learning, 2014)
Globally, lifelong education, has been identified as the most important driver of social, economic, political, technological, and environmental development. However, meaningful and realistic national development can only be achieved when sufficient attention is paid to strengthening the implementation of lifelong education. Therefore, it becomes imperative that governments and the private sectors in developing countries make substantial sacrifices in terms of resources, time, energy, and expertise toward the promotion of sustainable lifelong education. It is by this process that developing countries like Ghana can derive the fullest benefit from lifelong education and achieve the desired development objective of improving the quality of life of its citizens. (PDF) Strengthening Lifelong Education For Development: The Case of Ghana. Available from: https://www.researchgate.net/publication/319250534_Strengthening_Lifelong_Education_For_Development_The_Case_of_Ghana [accessed Sep 24 2018].
Keywords: Education; Development; Ghana; lifelong education